Ethnographic Fieldwork in Psychology: Lost and Found?. (February 2014) - Tanggaard, Lene
It is argued in the present article that ethnographic fieldwork can serve useful methodological ends within psychology and open the discipline to the cultural landscape of psychological phenomena in everyday life in social practices. Furthermore, a positive case is made for the soundness of ethnographic fieldwork. That is, rather than disputing the claim that qualitative methods can serve scientific ends, it is argued that ethnographic fieldwork is suitable for studying the constitution of psychological phenomena in social practices across time.